Analisis Transformasi IAIN Menjadi UIN Sebagai Upaya Meningkatkan Reputasi dan Posisi Global - Muhammad Ghafar; Sartika, Didi (IAIN Takengon, 2023)
The change from IAIN to UIN is not only about changing the name, but also about expanding the institution's views and contributions to providing more comprehensive education and scientific development, in line with the demands of the times and the needs of society. The transformation of IAIN (State Islamic Institute) into UIN (State Islamic University) is an important step in the context of increasing the reputation and global position of higher education institutions in Indonesia. The research method used is qualitative research, literature review. The results of this research are efforts to improve UIN's reputation and global position, namely strengthening the tri dharma of higher education, which is the main pillar, which must continue to be carried out to determine PTKIN's positioning in the international arena. Several strategies that can be considered to achieve UIN's global reputation and position, namely; provision of quality education, international partnerships, research and scientific publications, use of technology in learning, branding and marketing, focus on the quality of graduates, provision of supporting facilities, supporting diversity and inclusion, social and humanitarian activities, leadership programs and soft skill's development. Keywords: Transformation, Reputation, Global Position